Narrativas de gestores da educação superior: um olhar para a ética e a para a estética - Cazeri, Iara Garcia (2019)
This research aims to study the ethical and aesthetic dimension in the management of Higher Education, from the narratives of managers of a private higher education institution. In this way, it is sought to understand the ethical and aesthetic dimension in the management of Higher Education, having reference to the concept of ethics in Levinas (2008), extending to the sense of otherness. The study problem is configured as the sense of the ethical and aesthetic dimension of management in Higher Education in the view of managers of a private institution. The guiding question of the study is: which limits and possibilities of ethics to be improved through aesthetics, aiming at the development of autonomy and emancipation of the subjects, instead of management in Higher Education in a private institution? It starts from the hypothesis that the development of the autonomy and emancipation of the subjects happens through the improvement of the ethics and the aesthetic in the formative processes in the Higher Education. A part of the autobiographical narratives produced by the participants in the formative and investigative device "Berthbrock-Rosito," based on Josso (2004), is presented as a collection procedure. Passeggi (2010), Delory-Momberger (2010). Our methodological approach was based on the hermeneutical perspective in Gadamer (2000, 2003), in which the narratives of the five managers produced in the first stage of the "Patchwork Quilt" were analyzed with the possibility of understanding the meanings and the construction of the meanings attributed managers to tell about their experiences.